PKA/CREB and NF-κB pathway regulates AKNA transcription: A novel insight into T-2 toxin-induced inflammation and GH deficiency in GH3 cells - Liu, Xianglian; Huang, Deyu; Guo, Pu; Wu, Qinghua; Dai, Menghong; Cheng, Guyue; Hao, Haihong; Xie, Shuyu; Yuan, Zonghui; Wang, Xu (Toxicology, 2017)
Chronic exposure to low dose of T-2 toxin causes growth retardation and reduced body weight, resulting in economic losses. Excessive inflammatory cytokines and GH deficiency are important mechanisms that contribute to growth inhibition induced by T-2 toxin. However, the regulation of the inflammatory cytokines expecially IL-6, IL-1β, and TNF-α induced by T-2 toxin still remained unclear. The new transcription factor AKNA, belonging to AT-hook protein family, is closely associated with inflammation. However, it was unclear how AKNA regulate the expression of inflammatory cytokines, and there was no report on the role of AKNA in T-2 toxin mediated toxicity. Here, we investigated the role of AKNA in T-2 toxin-mediated inflammatory response and GH deficiency and the signal transduction pathway of AKNA. We showed that AKNA regulated by PKA/CREB and NF-κB pathway is a novel downstream molecular target in T-2 toxin-mediated inflammation and GH deficiency. T-2 toxin activates the PKA/CREB and NF-κB/p65 pathways, thereby promoting the direct binding of phospho-CREB and phospho-p65 to the AKNA promoter, thus inhibiting AKNA expression. GH and inflammatory cytokines (TNF-α, IL-1β, and IL-6) expression were significantly downregulated after AKNA silencing. Furthermore, the expression of differential genes induced by T-2 toxin in the rat pituitary was further confirmed by acute toxicity tests in rats, which was consistent with the results in GH3 cells. By histopathological analysis, we confirmed the pituitary might be a novel direct target organ of T-2 toxin. These findings provided new insights into the significant role of AKNA in T-2 toxin-induced inflammatory response and growth inhibition.
Keywords: Cyclic AMP Response Element-Binding Protein; down regulace; TNF-alfa; transkripční faktory; buněčné linie; fosforylace; proteinkinasy závislé na cyklickém AMP; promotorové oblasti (genetika); Nuclear Proteins; DNA vazebné proteiny; Rats; Transcription Factors; T-2 toxin; Down-Regulation; Promoter Regions, Genetic; Tumor Necrosis Factor-alpha; Interleukin-6; zánět; interleukin-6; Interleukin-1beta; Gene Silencing; jaderné proteiny; protein vázající cAMP responzivní element; Inflammation; T-2 Toxin; DNA-Binding Proteins; NF-kappa B; Cell Line; Animals; krysa rodu Rattus; Cyclic AMP-Dependent Protein Kinases; umlčování genů; Phosphorylation; interleukin-1beta; zvířata